Modeling R&D spillovers to productivity: The effects of tax policy - Thomas von Brasch; Ådne Cappelen; Håvard Hungnes; Terje Skjerpen (Statistics Norway, Research Department, 2020)
We study the role of R&D spillovers when modelling total factor productivity (TFP) by industry. Using Norwegian industry level data, we find that for many industries there are significant spillovers from both domestic sources and from technological change at the international frontier. International spillovers contributed with 38 per cent to the total growth in TFP from 1982 to 2018 while domestic channels contributed with 44 per cent. The remaining 18 per cent is due to interaction effects. We include these channels into a large-scale econometric model of the Norwegian economy to study how R&D policies can promote economic growth. We find that current R&D policies in the form of generous tax deductions have increased growth in productivity and income in the Norwegian economy. The simulation results lend some support to the view that there are fiscal policy instruments that may have very large multipliers, even in the case of a fully financed policy change.
Keywords: C32; C51; D24; E17; O32; 330; R&D spillovers; total factor productivity; innovation policies